Changes of Arctic landscape due to human impact, north part of Billefjorden area, Svalbard - Tomczyk, Aleksandra M.; Ewertowski, Marek (Quaestiones Geographicae, 2010)
This study present indications of human impact on selected components of environment in the vicinity of Petunia Bay, Billefjorden, central Spitsbergen. The area is easy accessible and has low restriction of human activity so it is a need for monitoring of the human impact there. Three groups of objects were inventoried. Large-scale objects are attached to industrial impacts (mainly mining and transport of natural resources) - mines, warehouses, blocks. They are clustered around the west side of the bay - Pyramiden settlement. Medium-scale objects (mainly linear forms - path, tracks) were created by transport as well as scientific and tourist activity. Small-scale impacts (campsites, firesites) were created mainly by scientists and tourists and scattered around whole study area. Industrial activity in this area took place between 1927 and 1998, but its tracks are persistent and hard to remove. Scientific and tourist movements also started at the beginning of the XX century, but nowadays the activities become more and more intensive.